SOCIOECONOMIC FACTORS AND HEALTHCARE ACCESS: THEIR ROLE IN THE MANAGEMENT AND OUTCOMES OF DIABETIC FOOT ULCERS - SINGH, AJIT; AGRAWAL, AMIT; ARORA, AMAN (International Journal of Current Pharmaceutical Research, 2024)
Objective: Diabetic foot ulcers (DFUs) are a significant complication of diabetes mellitus, affecting millions globally and presenting considerable challenges to healthcare systems. While clinical aspects of DFUs are well-documented, socioeconomic factors and healthcare access play crucial roles in their management and outcomes. This study investigates how socioeconomic status (SES), healthcare accessibility, and patient education influence DFU prevention, treatment, and prognosis. Methods: A prospective, cross-sectional observational study was conducted over 13 mo at the Department of General Surgery, Command Hospital (Western Command), Chandimandir. Fifty patients with DFUs were enrolled based on specific inclusion and exclusion criteria. Data were collected on demographic details, lifestyle habits, comorbidities, and specifics of diabetes and DFU. Ulcer characteristics, wound cultures, and outcomes were analyzed using SPSS version 21.0. Results: The study population had a mean age of 60.10 y, with a predominance of males (78%). Smoking and obesity emerged as significant risk factors, with smoking more prevalent among males and obesity more common in females. The distribution of ulcer locations and the microbial profile, dominated by Staphylococcus aureus, underline the complexity of DFU management. These findings highlight the influence of socioeconomic factors and healthcare access on DFU outcomes. Conclusion: Effective DFU management requires a holistic approach that extends beyond clinical treatment to address socioeconomic factors and healthcare access. Tailored interventions that consider these broader determinants of health are essential for improving DFU outcomes and patient quality of life. Addressing healthcare disparities can significantly reduce the burden of DFUs, creating a more equitable and effective framework for diabetes care.